k-Resilient Identity-Based Encryption in the Standard Model - HENG, S.-H. (2006)
We present and analyze an adaptive chosen ciphertext secure (IND-CCA) identity-based encryption scheme (IBE) based on the well studied Decisional Diffie-Hellman (DDH) assumption. The scheme is provably secure in the standard model assuming the adversary can corrupt up to a maximum of k users adaptively. This is contrary to the Boneh-Franklin scheme which holds in the random-oracle model.